Back-stepping robust trajectory linearization control for hypersonic reentry vehicle via novel tracking differentiator. Issue 9 (June 2016) - Shao, Xingling; Wang, Honglun
Abstract: This paper proposes a back-stepping robust trajectory linearization control (TLC) design for hypersonic reentry vehicle (HRV) attitude tracking problem from a novel tracking differentiator perspective. First, the attitude kinematics and dynamics for HRV is formulated and rewritten in feedback form with mismatched and matched uncertainties introduced by variations of various aerodynamic coefficients. Second, a sigmoid function based novel tracking differentiator (STD) with global fast convergence property, simple structure and chattering-free in differential estimation is developed to handle the "explosion of term" problem in back-stepping TLC design. In addition, dynamical performance and noise-attenuation ability of STD are analyzed in frequency domain by describing function method. Third, how to convert between sigmoid function based disturbance observer (SDO) and STD is given, and based on the estimates of uncertainties provided by SDO in attitude and angular rate loop, the back-stepping robust TLC is synthesized to track the respective commands in dual-loop. Then, the stability of the composite SDO-enhanced back-stepping TLC approach is established. Finally, extensive simulation results are presented to demonstrate the effectiveness of the proposed control strategy in improving disturbance attenuation ability and performance robustness against multiple uncertainties.